Determination of minimum inhibitory concentration of Azithromycin, Ofloxacin and Ceftriaxone in Ciprofloxacin resistant Salmonella causing enteric fever - Kawser, Shamima; Miah, Md. Ruhul Amin; Saleh, Ahmed Abu; Sabah, Khandker Md. Nurus; Begum, Tanzima (Bangladesh Journal of Medical Microbiology, 2013)
The therapeutic alternatives available for use against ciprofloxacin resistant enteric fever isolates in an endemic area are limited. The antibiotics currently available are the quinolones, third-generation cephalosporins and azithromycin. In this study, the MICs of various drugs were determined for 100 enteric fever isolates (72 Salmonella enterica serovar typhi and 28 Salmonella enterica serovar paratyphi A ). Ciprofloxacin resistant (1oo%) Salmonella strains were sensitive to ofloxacin and ceftriaxone showing MICs of 0.0078-2 g /ml and 0.0156-2g /ml respectively. Salmonella strains (98%) had MIC values 1-32 g /ml for azithromycin. These results indicate that ofloxacin and ceftriaxone may be convenient alternative antimicrobial agents for Salmonella isolates. DOI: http://dx.doi.org/10.3329/bjmm.v5i1.15818 Bangladesh J Med Microbiol 2011; 05 (01): 26-30